APPLICATION OF GEOGRAPHIC INFORMATION SYSTEM FOR THE POSTAL NETWORK ANALYSIS (Perner's Contacts, 2021)
The postal network is a comprehensive set of several subsets, namely, postal infrastructure (consisted of objects and means), transportation networks, and human resources. It is organized by specific considerations of every country, following practices outlined by national and international regulation. Geographic Information System is a tool specialized for spatial data and network analysis. It can help identify shortcomings in a network environment, conditioned by a specific set of criteria and provisions. Spatial data and characteristics of the postal network are taken into consideration. The research area’s transportation infrastructure and administrative data are also needed for quality analysis of the postal network. The application of GIS in this paper is made following one County’s example in the Republic of Croatia.
Keywords: postal network; GIS, spatial analysis; postal network organisation